Research on the electrical capacitance and electrical conductivity of char resulting from natural and treated wood - Mačiulaitis, Romualdas; Jefimovas, Andrejus; Lipinskas, Donatas (Journal of Civil Engineering and Management, 2014)
Wood is a material widely used for construction purposes and having quite a number of advantages. However, one of the major drawbacks of wood are its flammability. In case of fire in wooden buildings or constructions made of timber structures, the most noticeable feature of combustion is charring these structures. This property is important for identifying the cause of a fire. Therefore, it is necessary to relate charring timber structures with certain significant effects of fire such as its duration or temperature. It is also particularly important to identify whether timber has been treated with fire retardant solutions before the fire break-out. The values of electrical capacitance and conductivity for the media obtained from char resulting from natural wood and that treated with fire retardant solutions and dispersed in distilled water depending on heating time have been determined. Moreover, it has been stated that the electric conductivity of char resulting from natural wood is 100 times lower, and the electrical capacitance of such char is 1000 lower than those resulting from treated wood. The regression analysis of the obtained data has been performed. The empirical equations have been derived. The results of the conducted research have been summarised. Priority has been given to the application of the method evaluating electrical conductivity.